TINJAUAN ETIKA BISNIS SYARI’AH TERHADAP PRAKTEK OLIGOPOLI PADA PELAKU USAHA PAKAIAN DI PASAR KAWASAN WISATA RELIGI MAKAM GUS DUR JOMBANG: Vol 06 Nomer 02 September 2019 - Azizah, Ninik; Syaiin; Fitria, Norma (Irtifaq, 2019)
This article aims to find out and describe the views of shari’ah business ethics on the practice of oligopoly in clothing businesses in the Gus Dur Jombang tomb religious tourism market. With a qualitative approach to the type of field research, data from observations, interviews and documentation are analyzed deductively by taking theory or rules of shari'ah business ethics related to oligopoly, then the theory is drawn to the facts or facts of the case in the field. The results showed that the practice of oligopoly in the clothing business in the market of Gus Dur Jombang's tomb religious tourism area was seen as violating Shari'ah's business ethics. There are two categories of business actors with oligopolistic practices, both of which have the same goal, namely to seek maximum profits by harming and killing potential and reducing business results to control market share without the fulfillment of fair and balanced aspects. The obstacle faced by the management in the Market Management of Gus Dur Jombang tomb religious tourism area is not having the authority to manage the market located in the second zone (Dsn Seblak, Tebuireng and Kwaron) and the third zone (pondok Tebuireng). So that the management of the UPTD can not do anything except manage at the point of zone one. Keywords: Shari’ah Business Ethics, Oligopoly, Business Actor